Ethical publishing as resistance: Reflections from plaNext and the politics of knowledge and space - Feras Hammami (PlaNext)
What does it mean to publish ethically in a world where knowledge production is shaped by human rights violations, social inequalities, colonial legacies, and systemic exclusions? This reflection draws on ten years of experience with plaNext, an open access journal created by the Young Academics Network of the Association of European Schools of Planning to support early career scholars. It explores how ethical publishing can act as a form of resistance to dominant academic norms, the marginalization of alternative epistemologies, and the politicization of knowledge. Through personal and collective experiences, the article examines plaNext's commitment to academic freedom, equity, decolonisation, and inclusivity, expressed through practices such as voluntary management, half-blind peer review, and a justice-based ethical policy. It also addresses the challenges of sustaining these principles within the constraints of institutional expectations, the publishing industry, and global crises. Ethical publishing, it argues, is not about pretentious neutrality but about taking a principled stance in support of marginalized voices, critical scholarship, and transformative knowledge production. Whether this vision remains viable is an open question that plaNext and many other international journals must continue to examine.